Highly conductive and stretchable radiating element antenna using Silver Nanowires and Polydimethylsiloxane elastomers for body centric wireless communications applications - Basar, Hanis Danial (2017)
In this project, involve an antenna with a feedline fed. First antenna was made with an inset-fed and it is of uncommon materials; Silver Nanowires and Polydimethylsiloxane. The conductive radiator used is Silver Nanowires (AgNWs) and for substrate is Polydimethylsiloxane (PDMS) elastomers. The desired antenna was designed to be use on body-centric wireless communications (BWCWs) applications specifically to work in Industrial, Scientific and Medical (ISM) band. The simulation of the antenna was simulated by using the Computer Simulation Technology software (CST). Based on other journals reviewed, the most common element used for the radiating patch for an antenna is usually copper because of its high conductivity and cost. However, when compared to silver, the electrical and mechanical properties of silver is better than copper. When applied pressure, stretching, or bending into certain point the surface of copper is cracked but not to silver. There are several efforts made by previous research where the researchers applied another layer on the top and bottom to reduce the surface cracking such as PDMS-Fe304 and plastic substrate, and then sandwiched the antenna. In this thesis, there are tests where the simulation has three types of conditions; flat, bending environment; on x-plane and y-plane. These conditions are tested for both antennas to see the effects if the antenna were to apply onto clothes (off-body) or skin (on-body) for wearable applications. As for the results, the resonance frequency for normal or flat environment of the designed antenna shows it is operating at 2.45 GHz with low power reflected. While bending conditions, it has a slight different compare to normal condition, but it is still consider working at ISM band. Other than that, other parameters such as farfield, bandwidth, VWSR, E-field, H-field and directivity are also compared.